Pengenalan Peralatan Ground Based Navigation dan Global Navigation Satellite System Untuk Personel Bandar Udara di Indonesia - Purwaningtyas, Dian Anggraini (Politeknik Penerbangan Indonesia Curug, 2024)
The development of navigation equipment, both ground-based and satellite-based for flight operations, is the key to service, the development of air navigation technology needs to be known by stakeholders in flight operations, it is deemed necessary for personnel on duty at airports to know the development of air navigation technology, some of the equipment installed At airports there are provisions to be free from obstructions so that the equipment can operate properly by flight operational standards and conditions. This activity aims to provide airport staff with an introduction to aviation navigation technology. This activity was carried out online and was attended by 20 staff from airport service units in Indonesia. Based on the evaluation of the activity, it was found that the participants were able to understand the material, some participants felt that it was still necessary to provide visualization of the performance of navigation equipment because the activity was carried out online and required teaching material that used illustrations so that participants could maximize their understanding of aviation navigation technology.